Framework to manage suppliers for strategic alliances with a multicriteria method - Guarnieri, Patricia (2015)
Processes that identify top suppliers of new products or services and evaluate the performance of the existing suppliers are essential to strategic alliances. The objective of this article is to propose a framework to select partners for strategic alliances in supply chain management using a multi-criteria method. To reach this objective, the multi-criteria modeling procedure was used to detach the steps of a decision process, which comprises the methodology used in this article. To illustrate the use of the model, a numerical application, with characteristics from a small supermarket using the ELECTRE III method, was presented. The main contribution of the model proposed is to improve the process used to select suppliers for strategic alliances by considering multiple criteria called 'soft factors'. The proposed model suggests a systematic procedure that can reduce uncertainty in the decision process.